PENGEMBANGAN BUKU SAKU UNTUK MENINGKATKAN PERENCANAAN KARIER SISWA SMP NEGERI TULUNGAGUNG - Berta Azizah; Elisabeth Christiana (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
The general objective of this research is to produce a pocket book product to improve career planning that meets the eligibility criteria for pocket books in terms of material and design aspects, and can effectively help students improve career planning. While the specific purpose of this study is to collect empirical data to test the feasibility and effectiveness of pocketbooks. Pocket book products are said to be feasible if the contents are in accordance with the conceptual framework and are attractive in terms of design. Meanwhile, the effectiveness of the pocket book is seen from the product's ability to bring about the expected positive changes, namely increasing students' career planning. This research procedure uses the Borg and Gall research procedure which consists of ten stages. However, this study limits it to six stages of the procedure, namely initial research and data collection, planning and development, initial product development, field test (expert validation), revision I, and small group test. At the expert validation stage, material experts and media experts were involved. The data results related to the effectiveness of the product using one group experiment, namely one group pre-test post-test and statistically analyzed using the paired sample t-test formula. The test results show that the pocket book product developed is effective to use which can be proven by a significant increase in the level of realistic career planning to the subject after the application of the career pocket book.